Cloud Based Big Data Processing Approaches - Rashmi, G; Kumar, Sathish (International Journal of Computer Sciences and Engineering, 2025)
Nowadays Big data processing in cloud has become a challenging task. This paper describes the basics of cloud computing and current big-data processing approaches in cloud such as batch-based, stream-based, graph-based, DAG-based, interactive-based, visual-based and summarizes the strengths and weaknesses of these approaches in order to help the future big data research scholars to select the appropriate processing technique.